Pengaruh Profitabilitas, Ukuran Perusahaan, Financial Slack, Terhadap Carbon Emission Disclosure Dengan Tekanan Eksternal Sebagai Variabel Moderasi - Sri Alfiana; Mustakim Muchlis; Raodahtul Jannah (Academic Bright Collaboration, 2025)
This research aims to examine the effect of profitability, company size, and financial slack on carbon emission disclosure with external pressure as a moderating variable in infrastructure and energy sector companies. This study is a type of quantitative research, with the population and sample taken from infrastructure and energy sector companies listed on the Indonesia Stock Exchange (IDX). The method used for sampling is purposive sampling. The data obtained has been tested for classical assumptions, and the hypothesis testing methods used include multiple linear regression analysis and moderation regression analysis using the absolute difference method. The results of the tests in this study. This research found that profitability has a significant negative effect on carbon emission disclosure, company size has a significant positive effect on carbon emission disclosure, and financial slack has a significant positive effect on carbon emission disclosure. The analysis of the moderating variable shows that external pressure can moderate the effect of profitability and financial slack on carbon emission disclosure; however, external pressure has not been able to moderate the effect of company size on carbon emission disclosure. Based on the research results above, the implications of the research are as follows: Companies with higher profitability can use carbon emission disclosure as a legitimacy strategy to enhance their reputation in the eyes of stakeholders. Investors can use information about the proportion of shares traded and the level of carbon emission disclosure.